2009
DOI: 10.2214/ajr.07.3430
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MRI and Pulmonary MR Angiography of Sinus Venosus Defect and Partial Anomalous Pulmonary Venous Connection in Cause of Right Undiagnosed Ventricular Enlargement

Abstract: This article about cardiac MRI in adults with sinus venosus defect and PAPVC shows that cardiac MRI can reliably detect and quantify these lesions when other methods have not provided a complete diagnosis for the cause of right heart enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 24 publications
3
27
0
1
Order By: Relevance
“…It can therefore, help obviate the need for cardiac catheterisation. Our observations with regards to the clinical utility of CMRI for SV-ASD are supported by the results of Kafka and Mohiaddin [15]. They recently reported on a series of 19 patients with SV-ASD who underwent CMRI.…”
Section: Initial Clinical Experiencesupporting
confidence: 88%
See 1 more Smart Citation
“…It can therefore, help obviate the need for cardiac catheterisation. Our observations with regards to the clinical utility of CMRI for SV-ASD are supported by the results of Kafka and Mohiaddin [15]. They recently reported on a series of 19 patients with SV-ASD who underwent CMRI.…”
Section: Initial Clinical Experiencesupporting
confidence: 88%
“…In all cases, CMRI correctly identified the SV-ASD as well as any associated PAPVD. The authors concluded that CMRI can reliably detect and quantify these lesions when other methods have failed to provide a cause for right heart enlargement [15]. CMRI is also useful for follow-up after surgical repair of these lesions, where TTE windows are frequently suboptimal and also when there is discordance between clinical findings and TTE results.…”
Section: Initial Clinical Experiencementioning
confidence: 99%
“…Several numerical procedures have recently been proposed to evaluate flow patterns, determine the wall shear stress (WSS) distribution, and calculate pressure difference maps (Oshinski et al, 1995;Tyszka et al, 2000;Ebbers et al, 2001;Barker et al, 2010;Bock et al, 2010;Bock et al, 2011). These methods have shown the potential of 2D and 3D CINE PC-MRI for assessing different cardiovascular diseases (Wigström et al, 1999;Weigang et al, 2008;Boussel et al, 2009;Kafka and Mohiaddin, 2009;Markl et al, 2010;Cecchi et al, 2011;Frydrychowicz et al, 2011;Francois et al, 2012;).…”
Section: Introductionmentioning
confidence: 99%
“…Il n'est pas rare que l'examen IRM, demandé pour « suspicion de DVD » chez un patient avec cavités droites dilatées en échographie, fasse découvrir une communication interauriculaire (CIA) ou un retour veineux pulmonaire anormal (RVPA) [17]. C'est pourquoi il est de bonne règle de commencer l'examen IRM dans ce contexte par la mesure du rapport de débit Qp/Qs.…”
Section: Shunt Gauche-droiteunclassified